Enhancing Midwifery Students' Knowledge and Skills in Labor Dystocia via Webinar-Based Blended Learning: A Pre-experimental Study. - Bakhtiari, Afsaneh; Nasiri-Amiri, Fatemeh; Parvaneh, Monireh (Journal of Nursing & Midwifery Sciences, 2025)
Background: The risks of labor dystocia for both mothers and fetuses underscore the need for enhanced education. Despite the crucial role midwives play in managing labor dystocia, research in this area remains insufficient. Objectives: The present study aimed to evaluate the effect of webinar-based blended learning (BL) on midwifery students' knowledge and skills in managing labor dystocia. Methods: This pre-experimental study with a single-group pre-test/post-test design involved 26 seventh-semester midwifery students who had prior lecture-based instruction on labor dystocia and were exposed to webinar-based BL. The study was conducted in Babol, Iran in 2019. Assessments included a knowledge questionnaire, a skills checklist for labor dystocia in the clinical setting, and attitudes toward and satisfaction with webinar-based BL. The Wilcoxon test was used to assess changes in knowledge and skills before and after the intervention. Results: Significant improvements were observed in the average knowledge scores (from 9.56 ± 1.45 to 16.15 ± 2.35, P < 0.001) and clinical skill scores (from 2.35 ± 0.64 to 5.02 ± 0.70, P < 0.001) before and after the intervention. The students demonstrated highly positive attitudes toward the webinar-based BL method, with a mean attitude score of 28.56 ± 3.48. Additionally, their satisfaction with this approach was notably high, reflected in a mean score of 30.05 ± 4.06. Conclusions: The positive impact of webinar-based BL on learning outcomes, along with the improved attitudes towards success and increased student satisfaction, indicates that this teaching method should be integrated into midwifery education programs.